The dragon's hoard Stories from the Viking sagas - Don, Lari; Cate James (Illustrator) (London: Frances Lincoln Children's Books, 2016)
Eleven stories and folk tales from the Vikings, packed with warriors and battles, heroes and heroines, Berserkers, monsters, zombies and magic. It includes stories of a greedy dragon guarding a huge hoard of gold, a girl who becomes a swan to protect her warrior love in battle, and a polar bear brought to the king of Denmark as a gift
About the Viking sagas The dragon's hoard The swan warrior The Berserker's baby Tusker versus the earl The bear in chains The raven banner The boy in the bones Sailing to America Zombie on the roof Hunting Magnus Odin's riddles Where I found these stories
Keywords: English, Fiction